Application of failure mode and effect analysis (FMEA) and cause and effect analysis in conjunction with ISO22000 to an almond processing plant - Varzakas T.H.; Zakynthinos G.; Arvanitoyannis I.S. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
Failure Mode and Effect Analysis (FMEA) model has been applied for the risk assessment of almond manufacturing. A tentative approach of FMEA application to the almond industry was attempted in conjunction with ISO22000. Preliminary Hazard Analysis was used to analyse and predict the occurring failure modes in a food chain system (almond processing plant), based on the functions, characteristics and/or interactions of the processes, upon which the system depends. Critical Control Points have been identified and implemented in the cause and effect diagrams. Moreover, comparison of ISO22000 analysis with HACCP is carried out over almond processing and packaging. The main emphasis was put on the quantification of risk assessment by determining the Risk Priority Number (RPN) per identified processing hazard. Pasteurisation, fumigation with propylene oxide, packaging, storage and distribution and hulling/shelling were the processes identified as the ones with the highest RPN (240, 225, 180, 144, respectively) and corrective actions were undertaken. Following the application of corrective actions, a second calculation of RPN values was carried out leading to considerably lower values (below the upper acceptable limit of 130). It is noteworthy that the application of Ishikawa (Cause and Effect or Tree diagram) led to converging results thus corroborating the validity of conclusions derived from risk assessment and FMEA. Therefore, the incorporation of FMEA analysis within the ISO22000 system of an almond processing plant is considered imperative.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)